Historia Katedry Teorii i Filozofii Prawa - Helios, Joanna; Jedlecka, Wioletta; Bator, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
In this article the history of the Department of the Theory and Philosophy of Law is presented. The Department of Theory and Philosophy of Law is an organizational unit of the Faculty of Law, Administration and Economics of the Wrocław University, headed since 2005 by Prof. Andrzej Bator.The tradition of the Department dates back to the times of Prof. Stanisław Hubert 1905–1983 who, thanks to his great knowledge and the ability to win over pupils and partners, as well as his openness to new research fields, initiated the development of the theory of state and law at the Wrocław centre.Teaching and organizational scientific activities have been included in the work of the Department from the moment of its establishment until today. The article presents the profiles of employees of the Department and their individual contributions to its development. It concentrates on the analysis of individual research plains e.g. European legal culture, external and internal integration of jurisprudence, the rule of law and the European legal culture.
Keywords: Katedra Teorii i Filozofii Prawa; Wydział Prawa Administracji Ekonomii UWr; historia